2012
DOI: 10.1007/s10965-011-9739-7
|View full text |Cite
|
Sign up to set email alerts
|

p-benzoquinone diimines and thiophene based alternating copolymers: organometallic catalyzed syntheses and elementary characterization

Abstract: A series of alternating polymers, which were prepared by coupling of N, N'-dichloro-benzoquinonediimine (a) or 2, 5-dimethyl-N, N'-dichloro-benzoquinonediimine (b) with Grignard reagents of thiophene, were successfully prepared using Ni(II) complexes as catalyst with moderate yields (54-88%) and molecular weights (4.3-7.0×10 3 ). The basic properties of the obtained copolymers were characterized by FT-IR, 1 H NMR, UV-vis absorption, cyclic voltammetry, thermal analysis and Gel permeation chromatography (GPC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Compared with polymers synthesized by Suzuki and Stille polymerization, the molecular weight of the polymers obtained in this work and synthesized by the same polymerization method in previous reports was not high enough. One reason is the ease of homo‐coupling during polymerization.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Compared with polymers synthesized by Suzuki and Stille polymerization, the molecular weight of the polymers obtained in this work and synthesized by the same polymerization method in previous reports was not high enough. One reason is the ease of homo‐coupling during polymerization.…”
Section: Resultsmentioning
confidence: 57%
“…Many sorts of polymers have been synthesized by di‐functionalized thiophene Grignard reagents. However, the molecular weight obtained in the literature is mainly around 10.0 kDa . There are many reasons for researchers to avoid using Kumada coupling in a polymerization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…7 Several authors have reported the polymerization of polyanthraquinones and poly(p-benzoquinone) through organometallic polycondensation reactions. 8,9 Various results have been reported, based on the mode of synthesis of donor-acceptor polymers and the mechanism of polymerization, but the details regarding the control of the structure as well as morphology resulting from the synthetic conditions are still unexplored, and they are not well-explained even by computational studies. Hence, with the aim to investigate the inuence of polymerization conditions on the electronic structure, opto-electronic properties as well as the morphology of donor-acceptor polymers, the present work reports p-conjugated oligomers composed of thiophene (acceptor) and benzoquinone (donor) units synthesized by different chemical polymerization methods: magnetic stirring, ultrasonication and microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%